Differences Attract: An Experimental Study of Focusing in Economic Choice - Ola Andersson; Jim Ingebretsen Carlson; Erik Wengström (Lund University, School of Economics and Management, Department of Economics, 2016)
Several recent models of choice build on the idea that decision makers are more likely to choose an option if its attributes stand out compared to the attributes of the available alternatives. One example is the model of focusing by Köszegi and Szeidl (2013) where decision makers focus disproportionally on the attributes in which the available options differ more, implying that some attributes will be overweighted. We test this prediction in a controlled experiment. We find that subjects are more likely to make inconsistent choices when we manipulate the choice set by adding new options that are unchosen, but affect the maximal difference in attributes among the options. Hence, our results suggest that there exists a focusing effect.
Keywords: C91; D03; D12; 330; Individual decision making; focus; attention; salience; decoy; experiments